2015
DOI: 10.1063/1.4927708
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic defect formation in peptide self-assembly

Abstract: In contrast to extensively studied defects in traditional materials, we report here a systematic investigation of the formation mechanism of intrinsic defects in self-assembled peptide nanostructures. The Monte Carlo simulations with our simplified dynamic hierarchical model revealed that the symmetry breaking of layer bending mode at the two ends during morphological transformation is responsible for intrinsic defect formation, whose microscopic origin is the mismatch between layer stacking along the side-cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The influence of r s , the attraction between neighboring layers, to the selfassembled morphology was calculated and discussed in the supplementary material. 30 Although most parts of our results qualitatively agree with Aggeli's model, since the primary layer in our model is allowed to deform, in agreement with the experimental observation, in regime 4 our model results in a tube-like structure with a defect (Fig. S2), rather than a twisted ribbon by Aggeli's model.…”
Section: -6951/2015/107(4)/043701/5supporting
confidence: 79%
“…The influence of r s , the attraction between neighboring layers, to the selfassembled morphology was calculated and discussed in the supplementary material. 30 Although most parts of our results qualitatively agree with Aggeli's model, since the primary layer in our model is allowed to deform, in agreement with the experimental observation, in regime 4 our model results in a tube-like structure with a defect (Fig. S2), rather than a twisted ribbon by Aggeli's model.…”
Section: -6951/2015/107(4)/043701/5supporting
confidence: 79%
“…The increase in PSERS intensity after annealing can be attributed to several complementary effects. First, an apparently increased surface area [visible in SEM images (Figures bi–iii and S1)] provides more opportunity for probe molecule attachment and potentially higher Raman signals. Second, as shown in Figure biv, there was an associated change in wettability from hydrophilic to less hydrophilic with increasing temperature, as mentioned earlier.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] Many theoretical works have further demonstrated that the competition between the intra-and inter-sheet interactions determines the morphology of a laminated structure composed of cross-β sheets. [30][31][32] Quantitative information such as the bond stiffness and the compositions of the intermolecular forces is essential for understanding the nanomechanics and morphology of peptide nanostructures. Similar to covalent bond stiffness, the intermolecular bond stiffness is a measurement of the resistance offered by the structure to the deviation from its equilibrated structure stabilized by the non-covalent force.…”
Section: Introductionmentioning
confidence: 99%